Progressive natural wilting of guava plants during different months - B.K. PANDEY, A.K. MISRA and (Indian Phytopathology, 2002)
During 1996-98, natural wilting of guava (Psidium guajava) plants at Rehmankhera Experimental Farm, Lucknow (Uttar Pradesh), was recorded throughout the year at regular weekly intervals. Results indicated that wilting starts from August, increases during September-October, with maximum wilting during October. Although the yellowing symptom starts from August onwards, maximum yellowing was recorded during December. Some plants which show slight yellowing symptom, but resist wilting, start recoveringfrom December onwards. Maximum recovery of plants was seen during January, and by April, the plants which only show yellowing symptom but resist wilting, recover fully and develop a new flush. On analysing the weather data for 1996-98, it was observed that higher rainfall during July-September, maximum temperature around 31.5C-33.5â„ƒ, minimum temperature around 23-25â„ƒ and high humidity above 76% were conducive for the development of wilt in guava plants. In general, plants took a maximum of two monthsfor complete wilting after the appearance of the first visible symptom; however, the minimum time taken for complete wilting was only 16 days and the maximum was 195 days.